LEMON GRASS ESSENTIAL OIL A NATURAL SHIELD AGAINST BACTERIA AND CANCER (The Research of Medical Science Review, 2024)
The essential oil derived from lemongrass (Cymbopogon citratus) has long been revered for its aromatic and medicinal properties, playing a significant role in traditional medicine across various cultures. This review comprehensively explores the therapeutic potential of lemongrass essential oil, with a focus on its antibacterial, antimicrobial, and anticancer activities. The chemical composition of lemongrass essential oil, prominently featuring compounds such as citral, is examined, considering variations influenced by geographical factors and extraction methodologies. The antibacterial activities of lemongrass essential oil are elucidated, encompassing its efficacy against a spectrum of bacteria. Mechanisms of action, including cell membrane disruption and interference with bacterial enzymes, are discussed, alongside potential synergies with conventional antibiotics. In the realm of antimicrobial activities, the review surveys the literature on lemongrass essential oil's potential as an agent against fungi and other microorganisms, highlighting its role in preventing the growth of pathogenic microbes. The anticancer properties of lemongrass essential oil are explored, with a focus on studies investigating its impact on cancer cells. Cellular and molecular mechanisms, including apoptosis induction and potential anti-inflammatory effects, are dissected. The review bridges preclinical and clinical studies, summarizing findings from in vitro and in vivo investigations. Clinical trials assessing the therapeutic potential of lemongrass essential oil are considered, providing a comprehensive view of its translational applications. Safety concerns and potential side effects are addressed, emphasizing the importance of proper usage and adherence to safety guidelines